Right For Me: protocol for a cluster randomised trial of two interventions for facilitating shared decision-making about contraceptive methods. Issue 10 (22nd October 2017) - Thompson, Rachel; Manski, Ruth; Donnelly, Kyla Z; Stevens, Gabrielle; Agusti, Daniela; Banach, Michelle; Boardman, Maureen B; Brady, Pearl; Colón Bradt, Christina; Foster, Tina; Johnson, Deborah J; Li, Zhongze; et al.
Abstract : Introduction: Despite the observed and theoretical advantages of shared decision-making in a range of clinical contexts, including contraceptive care, there remains a paucity of evidence on how to facilitate its adoption. This paper describes the protocol for a study to assess the comparative effectiveness of patient-targeted and provider-targeted interventions for facilitating shared decision-making about contraceptive methods. Methods and analysis: We will conduct a 2×2 factorial cluster randomised controlled trial with four arms: (1) video+prompt card, (2) decision aids+training, (3) video+prompt card and decision aids+training and (4) usual care. The clusters will be clinics in USA that deliver contraceptive care. The participants will be people who have completed a healthcare visit at a participating clinic, were assigned female sex at birth, are aged 15–49 years, are able to read and write English or Spanish and have not previously participated in the study. The primary outcome will be shared decision-making about contraceptive methods. Secondary outcomes will be the occurrence of a conversation about contraception in the healthcare visit, satisfaction with the conversation about contraception, intended contraceptive method(s), intention to use a highly effective method, values concordance of the intended method(s), decision regret, contraceptive method(s) used, use of a highly effective method, use of the intended method(s), adherence, satisfaction with the method(s) used, unintended pregnancy and unwelcome pregnancy. We will collect study data via longitudinal patient surveys administered immediately after the healthcare visit, four weeks later and six months later. Ethics and dissemination: We will disseminate results via presentations at scientific and professional conferences, papers published in peer-reviewed, open-access journals and scientific and lay reports. We will also make an anonymised copy of the final participant-level dataset available to others for research purposes. Trial registration number: ClinicalTrials.gov Identifier: NCT02759939 .